A new polytypic species of the genus Uromastyx MERREM 1820 (Reptilia: Squamata: Agamidae: Leiolepidinae) from southwestern Arabia - Wilms, Thomas M.; Schmitz, Andreas (Zootaxa, 2007)
We describe Uromastyx yemenensis sp. nov. from south-western Arabia, comprising two geographic subspecies, U. y. yemenensis and U. y. shobraki ssp. nov. The new species is a member of the Uromastyx ocellata species group, closely related to U. benti. It is differentiated from its sister taxon by smaller scales around midbody and smaller ventrals. The new species is restricted to the extreme south-western tip of the Arabian Peninsula. The western populations of U. yemenensis differ genetically and are constantly distinct in respect to their colour pattern and are therefore recognized as a subspecies.